Quarterly Projection Model for Vietnam : A Hybrid Approach for Monetary Policy Implementation - Epstein, Natan (IMF Working Papers; Working Paper ;, 2022)
We present a newly developed Quarterly Projection Model (QPM) for Vietnam. This QPM represents an extended version of the canonical New Keynesian semi-structural model, accounting for Vietnam-specific factors, including a hybrid monetary policy framework. The model incorporates the array of policy instruments, specifically interest rates, indicative nominal credit growth guidance, and exchange rate interventions, that the authorities employ to meet the primary objective of price stability. The calibrated model embeds a theoretically consistent monetary transmission mechanism and demonstrates robust in-sample forecasting accuracy, both of which are important prerequisites for the richer analysis and forecast-based narratives that support a forward-looking monetary policy regime.